Job stress, sexual harassment, self-harm behavior, and suicidal ideation among military personnel in Taiwan - Huei-Ting Jin; Yi-Ching Lin; Carol Strong (Wolters Kluwer Medknow Publications, 2018)
Introduction: The aim of this study was first to estimate the prevalence of having self-harm behavior and suicidal ideation in a sample of military personnel. Second, we examined whether work stress, sexual harassment experiences, and depression were associated with suicidal ideation and self-harm behavior. Methods: A cross-sectional survey was conducted in Taiwan between January and April 2016. Sample was recruited from large military bases in Taiwan, including army, navy, and air force using convenience sampling. Self-reported data on job stress, sexual harassment experiences, self-harm behavior, and suicidal ideation were collected. Multiple logistic regression was used to determine the risk factors associated with having had self-harm behavior or suicidal ideation. Results: Of 513 individuals surveyed, 4.5% had self-harm behavior in the past 12 months and 9% had considered suicide. The majority of the sample were male (81.9%), between 20 and 29 years old (87.7%), voluntary military service (79.7%), and single or not married (90.8%). A higher level of sexual harassment experiences, higher level of perceived work stress, interpersonal relationship, and a lower level of job satisfaction were associated with self-harm behaviors. In multivariate analysis, gender, education, perceived work stress, sexual harassment, and depression were significantly associated with having had considered suicide in the past 12 months. Discussion: Our study highlighted the importance of acknowledging the vulnerability of the military work environment, including self-harming tendencies and sexual harassment. Education and training to ensure gender equality should be provided through appropriate channels.